Agricultural R&D in Paraguay: Policy, investments, and institutional Profile - Beintema, Nienke M.; Zambrano, Patricia; Nunez, Mario; Pardey, Philip G. (International Food Policy Research Institute, 2000)
By world, and even regional standards, Paraguay’s agricultural R&D investments and institutions are comparatively small and almost entirely dependent upon government and donor funding. The institutional structure has remained virtually unchanged over the past three decades, with the majority of research conducted by the crop and livestock directorates of the Ministry of Agriculture and Livestock.